Accuracy Analysis of Spectral Velocimetry for the Solar Doppler Difference Navigation - Shuying Huang; Zhiwei Kang; Jin Liu; Xin Ma (IEEE Access, 2021)
The accuracy of spectral velocimetry is an important performance index for the solar Doppler difference navigation. In order to analyze the influence of spectral variation on the accuracy of velocity measurement, we establish a velocimetry model based on the solar Doppler difference navigation, and propose a velocity accuracy analysis method. In this method, the reflected noise is filtered by wavelet transform, and then the high-resolution cross-correlation is used to solve the redshift value, so as to accurately calculate the velocity of the spacecraft. Combining the existing solar spectrum and Martian reflectance data, the 13 most obvious absorption lines are selected for velocity simulation and calculation. The experimental results show that the velocity accuracy of Doppler difference navigation can reach 0.1312m/s. The width and depth of the spectral line, the planetary reflectivity, as well as the sunlight fluctuations and the reflected noise will all have a certain impact on the spectral velocimetry for the Solar Doppler Difference Navigation.